Le classement des archives de familles en Belgique - Van Nieuwenhuysen, Andrée (Archives et bibliothèques de Belgique (ABB), 1998)

L'archivistique néerlandaise et la généalogie - Dekker, Cornelis (Archivum, 1992)

Les archives notariales et leur utilisation en généalogie : l'exemple du minutier central de Paris - Etienne, Geneviève (Stemma, 1982)

Les généalogistes et les Archives - Wolff, Christian (Gazette des archives, 1979)
Genealogists and archives. Difficultes encountered and examples of solutions adopted by several archive institutions to meet the increasing number of genealogists. The growing importance of this category of researchers and the risks which they inflict on the preservation of documents make it advisable that archivists adopt a common attitude in their relations with genealogists. Better organisation and discipline of genealogists themselves would make these relations easier.